Konsep Dakwah Al-Ba>hy Al-Khauwly - Kusnadi Kusnadi; Faridah Faridah; Ahmad Sukardi (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2020)
This paper aims to describe how followers of Islam have their own concepts in preaching especially shaykhs, scholars, clerics, religious teachers and others in da'wah. Each individual preacher has a concept and characteristic in his preaching, especially Syekh Al-Bahy Al-Khauly. from this description the author discusses how the concept of da'wah in Al-Bahy Al-Khauly. The method used in this study uses a library research method or approach. The concept of da'wah Al-Bahy Al-Khauly in the book tazkirah du'at in general, there are two things, first a preacher who wrestles in the world of da'wah and second must have a good mood.